Self-report prospective memory problems in people with stroke. (28th October 2014) - Man, David; Yip, Calvin; Lee, Grace; Fleming, Jennifer; Shum, David
Abstract: Background and purpose : Prospective memory (PM) is a common problem which can limit performance of basic and instrumental activities of daily living in patients with stroke. This study compared self-report PM failures between older and younger people with stroke, examined differences in perceptions of PM failures between people with stroke and relatives, relationships between these PM failures and functional performance. Methods : A total of 105 patients with stroke, 65 relatives and 112 healthy controls were recruited. Both the patients with stroke and controls were further divided into an older (age > 55 years) and a younger (age ≤ 55 years) group. Data for patients with stroke and relatives were obtained via the Brief Assessment of Prospective Memory (BAPM), Basic Activity of Daily Living (BADL) related Modified Barthel Index (MBI) and Lawton Instrumental Activities of Daily Living (Lawton IADL) Scale. Healthy controls' data were also collected. Results : The older stroke group had significantly higher BAPM total scores and BADL and IADL sub-scale scores than the younger group. Difference in perceptions of the patients' self-report of PM failures and their relatives' report was significant for the IADL sub-scale. Self-report of PM failure was significantly related to functional BADL and IADL measures. Conclusions : Results highlight the impact of PM failures in patients with stroke and their assessment, management and rehabilitation of these patients.